1987
DOI: 10.1159/000238524
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Experimental Candidiasis, Cryptococcosis, Aspergillosis and Wangiellosis in Mice

Abstract: Combination pairs of 5-fluorocytosine (5-FC) + itraconazole (Itra), 5-FC + fluconazole (Flue), and amphotericin B (Amph B) + Itra were administered to mice with experimental candidiasis, cryptococcosis, aspergillosis and wangiellosis with a variety of combination ratios. The life-prolonging effect of the combinations was compared with the effect of each partner administered alone and with a double dosage. Using the U test of Mann and Whitney, the effects of the concentration were classified as synergistic, add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 13 publications
6
72
0
Order By: Relevance
“…Several studies have suggested that different concentrations of each drug in combination can be associated with results that range from synergy to antagonism (19,157,161 (24,166,213) have employed standard antifungal doses in combinations that are consistent with maximally tolerated doses used in monotherapy. This approach seems logical given limited resources.…”
Section: Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have suggested that different concentrations of each drug in combination can be associated with results that range from synergy to antagonism (19,157,161 (24,166,213) have employed standard antifungal doses in combinations that are consistent with maximally tolerated doses used in monotherapy. This approach seems logical given limited resources.…”
Section: Rationalementioning
confidence: 99%
“…Investigations that have not confirmed synergy (78,80,161) VOL. 48,2004 MINIREVIEW 697 (14) Improved (3,50,61,157), similar (14,50,60,212), or worse (89) survival Reduced tissue burden (50,78,101,212) Combination associated with better survival than monotherapy and was consistent over a range of doses (3); effects more pronounced at lower doses (101), and single agents were very effective at higher doses alone; 5FC ϩ KTC rarely cleared tissues better than either agent alone (150); hamsters with combination did worse than with ITC alone (89); ITC ϩ 5FC performed similarly to ITC ϩ AmB and better than ITC or 5FC monotherapy in guinea pigs (212); with 10 days of treatment of mice, combination prolonged survival more than either agent alone but not when treatment was limited to 5 days (157); PSC combination not better than monotherapy in terms of survival but better than monotherapy in reducing fungal counts in brain tissue (14) Humans FLC (48,102,124,193,223) Good clinical success (48,102,193 FLC: addition of AmB to FLC had dramatic impact on yeast burden in brain tissue b , but survival with AmB was 100%; effects on survival were greatest at highest dosages of azole-AMB (2,158); improved survival at lower doses of ITC ϩ AmB, but survival was worse when higher doses were used (157); FLU preexposure did not reduce subsequent AmB activity (13) Humans-case report (47) Case report of a woman with meningitis who responded to this combination after failing AmB used lower concentrations of flucytosine and amphotericin B only or used strains with reduced susceptibility to flucytosine, which may have influenced or biased their ability to characterize the full spe...…”
Section: Neoformans (I) In Vitro Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Azoles inhibit ergosterol synthesis and thereby eliminate the target for the activity of amphotericin B [13,14). This antagonism has been widely confirmed for Candida species and aspergilli on the basis of data from in vitro studies [13][14][15][16] as well as those from experimental infections [16][17][18][19]. Published data on the antifungal activity of fluconazole plus amphotericin B are admittedly scarce, yet it is not surprising that such antagonism can be brought about without difficulty ( figure I).…”
mentioning
confidence: 93%